Fasting/Refeeding Cycles Prevent Myocardial Dysfunction and Morphology Damage in the Spontaneously Hypertensive Rats - Pinotti, Matheus Fécchio (2018)
AbstractBackground: Caloric restriction is known to impair the cardiac function and morphology in hypertrophied hearts of spontaneously hypertensive rats (SHR); however, the influence of fasting/refeeding (RF) is unknown.Objective: To investigate the fasting/refeeding approach on myocardial remodeling and function. In addition, the current study was designed to bring information regarding the mechanisms underlying the participation of Ca2+ handling and b-adrenergic system.Methods: Sixty-day-old male SHR rats were submitted to food ad libitum (C), 50% food restriction (R50) or RF cycles for 90 days. Cardiac remodeling was assessed by ultrastructure analysis and isolated papillary muscle function. The level of significance considered was 5% (a = 0.05).Results: The RF rats presented lower cardiac atrophy than R50 in relation to C rats. The C rats increased weight gain, R50 maintained their initial body weight and RF rats increased and decreased weight during RF. The RF did not cause functional impairment because the isotonic and isometric parameters showed similar behavior to those of C. The isotonic and isometric cardiac parameters were significantly elevated in RF rats compared to R50 rats. In addition, the R50 rats had cardiac damage in relation to C for isotonic and isometric variables. While the R50 rats showed focal changes in many muscle fibers, the RF rats displayed mild alterations, such as loss or disorganization of myofibrils.Conclusion: Fasting/refeeding promotes cardiac beneficial effects and attenuates myocardial injury caused by caloric restriction in SHR rats, contributing to reduce the cardiovascular risk profile and morphological injuries. Furthermore, RF promotes mild improvement in Ca2+ handling and b-adrenergic system.